Booster shot of inactivated SARS‐CoV‐2 vaccine induces potent immune responses in people living with HIV. Issue 1 (3rd January 2023) - Zhan, Haoting; Gao, Huixia; Liu, Yongmei; Zhang, Xihong; Li, Haolong; Li, Xiaomeng; Wang, Lijing; Li, Chen; Li, Beilei; Wang, Yuling; Dai, Erhei; Li, Yongzhe
Abstract: This study aimed to investigate the immunogenicity to SARS‐CoV‐2 and evasive subvariants BA.4/5 in people living with HIV (PLWH) following a third booster shot of inactivated SARS‐CoV‐2 vaccine. We conducted a cross‐sectional study in 318 PLWH and 241 healthy controls (HC) using SARS‐CoV‐2 immunoassays. Vaccine‐induced immunological responses were compared before and after the third dose. Serum levels of IgG anti‐RBD and inhibition rate of NAb were significantly elevated at the "post‐third dose" sampling time compared with the pre‐third dose in PLWH, but were relatively decreased in contrast with those of HCs. Induced humoral and cellular responses attenuated over time after triple‐dose vaccination. The neutralizing capacity against BA.4/5 was also intensified but remained below the positive inhibition threshold. Seropositivity of SARS‐CoV‐2‐specific antibodies in PLWH was prominently lower than that in HC. We also identified age, CD4 cell counts, time after the last vaccination, and WHO staging type of PLWH as independent factors associated with the seropositivity of antibodies. PLWH receiving booster shot of inactivated vaccines generate higher antibody responses than the second dose, but lower than that in HCs. Decreased anti‐BA.4/5 responses than that of WT impede the protective effect of the third dose on Omicron prevalence.